Fault locking of the Qilian–Haiyuan fault zone before the 2022 Menyuan Ms6.9 earthquake and its seismic hazards in the future - Liu, Lei; Zhuang, Wenquan; Ji, Lingyun; Zhu, Liangyu; Jiang, Fengyun (Frontiers in Earth Science, 2022)
By using GPS-derived velocities of 2015–2021 and a negative dislocation program, we inverted the locking degree and slip rate deficit in the Qilian–Haiyuan fault zone, and combined with the distribution of small earthquakes in the fault, we studied the characteristics before the 2022 Menyuan MS6.9 earthquake and analyzed the future seismic hazards of each segment within this fault zone. The regional crustal deformation pattern is discussed with regard to the fault slip rate and regional strain rate field. The preliminary results show that before the earthquake, the seismogenic faults were strong locked, with a high locking depth, the slip rate deficit was large, and the distribution of small earthquakes was relatively few, these characteristics are closely related to the occurrence of strong earthquakes, according to the aftershock relocation results, further, it is believed that the earthquake may link the Lenglongling and Tuolaishan faults into a large strike-slip fault. The Jinqianghe fault, the Lenglongling fault, and the eastern segment of the Tuolaishan fault are strongly locked, with high locking depth and large slip rate deficit, combined with the occurrence of small earthquakes and the locking degree before the 2022 Menyuan MS6.9 earthquake, indicate that the eastern segment of the Tuolaishan fault is highly likely to have strong earthquakes in the future, which requires further attention. In addition, the strike-slip rate of the Qilian–Haiyuan fault zone is mainly between 3.9–4.3 mm/yr, the overall movement of the fault is consistent, and the compressional rate gradually decreases from 2.9 mm/yr in the western segment to 1 mm/yr in the eastern segment; the fault compressional rate may be related to the crustal shortening (formation basin and uplift mountain). Therefore, the present-day crustal deformation in the northeastern margin of the Tibetan Plateau is mainly distributed in the shortened region of the crust on the Qilian Shan area and left-lateral strike-slip localized on the Qilian–Haiyuan fault zone.